Zoliflodacin, A Novel Antimirobial Agent Against neisseria Gonorhoeae: A Systematic Rreview of Quasi-Experimental Studies - Matthew, Franklind; Stella, Maureen Miracle; Tandarto, Kevin; Regina, Regina (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: The gram-negative bacteria Neisseria gonorrhoeae is the source of the STI known as gonorrhea. N. gonorrhoeae can adapt well to humans as a host and become a pathogen with sophisticated mechanisms to avoid the innate immune response as well as suppress the adaptive immune response. Lately, zoliflodacin was shown to have antibacterial activity against N. gonorrhoeae. Purpose: The aim of this study is to evaluate the antibacterial activity of zoliflodacin against N. gonorrhoeae. Methods: We followed the PRISMA 2020 guidelines to systematically search and collect literature in the following databases: ProQuest, EBSCOhost, PubMed, ScienceDirect, Taylor&Francis, SAGE, JSTOR, and Wiley, without time limitation (until October 9th,  2022). Titles and abstracts were reviewed for relevance. The inclusion criteria were original article written in English that investigated the effects of zoliflodacin in patients with gonorrhea. From 177 studies, we retrieved five studies for this study, published between 2015 and 2021. Results: Zoliflodacin was highly active in vitro against N. gonorrhoeae isolates from European countries, China, Thailand, and South Africa, and also showed potent antimicrobial activity against multi-resistant N. gonorrhoeae isolates in South Korea. There were three different kinds of minimum inhibitory concentration (MIC) evaluated, with the following results: modal MIC (0.064-0.25 Î¼g/mL), MIC50 (0.03-0.125 Î¼g/mL), and MIC90 (0.06-0.25 Î¼g/mL). There was no cross-resistance to antimicrobials currently or previously used for gonorrhea treatment. This MIC range could be used for further studies.